2017
DOI: 10.1371/journal.pmed.1002329
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of mother-to-child transmission of HIV and Syphilis (EMTCT): Process, progress, and program integration

Abstract: Melanie Taylor and colleagues discuss progress towards eliminating vertical transmission of HIV and syphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 9 publications
1
70
0
5
Order By: Relevance
“…Dual HIV and syphilis RDT testing in countries was prioritized by the WHO for the elimination of mother-to-child transmission (MTCT) of HIV and syphilis by 2020 32,33 , but a recent review showed that while Prevention of Mother to Child Transmission (PMTCT) programmes for HIV have resulted in a dramatic decrease in the number of HIV-positive infants in sub-Saharan Africa, the rate of syphilis screening of pregnant women in the same countries has remained at unacceptably low levels of approximately 30% (ref. 34 ).…”
Section: Malariamentioning
confidence: 99%
“…Dual HIV and syphilis RDT testing in countries was prioritized by the WHO for the elimination of mother-to-child transmission (MTCT) of HIV and syphilis by 2020 32,33 , but a recent review showed that while Prevention of Mother to Child Transmission (PMTCT) programmes for HIV have resulted in a dramatic decrease in the number of HIV-positive infants in sub-Saharan Africa, the rate of syphilis screening of pregnant women in the same countries has remained at unacceptably low levels of approximately 30% (ref. 34 ).…”
Section: Malariamentioning
confidence: 99%
“…By 2012, these efforts had contributed to a reduction in global adverse pregnancy outcomes due to MTCT of syphilis to 350,000, including 210,000 perinatal deaths, and decreased the rates of maternal and congenital syphilis decreased by 38% and 39%, respectively 23,24 . In 2015, Cuba became the first country to be validated for having achieved elimination of MTCT of HIV and syphilis 54 . Subsequently, Thailand, Belarus and four United Kingdom Overseas Territories (Bermuda, the Cayman Islands, Montserrat and Antigua) was validated for elimination of MTCT of HIV and syphilis, Moldova was validated for elimination of MTCT of syphilis, and Armenia was validated for elimination of MTCT of HIV.…”
Section: Epidemiologymentioning
confidence: 99%
“…Congenital syphilis is a consequence of untreated syphilis in the mother. More than half of congenital syphilis cases resulted in premature labor, miscarriage, stillbirth, low birth weight, and even death of the neonates . The condition is preventable when all pregnant women are screened and treated appropriately .…”
mentioning
confidence: 99%
“…More than half of congenital syphilis cases resulted in premature labor, miscarriage, stillbirth, low birth weight, and even death of the neonates. 1 The condition is preventable when all pregnant women are screened and treated appropriately. 2 This has led the World Health Organization (WHO) to set a goal for the elimination of mother-tochild transmission of syphilis to 50 cases per 100 000 live births by 2030.…”
mentioning
confidence: 99%